The role of microbiome in rheumatoid arthritis treatment. (July 2019) - Bodkhe, Rahul; Balakrishnan, Baskar; Taneja, Veena
Rheumatoid arthritis (RA) is an autoimmune disorder with multifactorial etiology; both genetic and environmental factors are known to be involved in pathogenesis. Treatment with disease-modifying antirheumatic drugs (DMARDs) plays an essential role in controlling disease progression and symptoms. DMARDs have immunomodulatory properties and suppress immune response by interfering in various pro-inflammatory pathways. Recent evidence has shown that the gut microbiota directly and indirectly modulates the host immune system. RA has been associated with dysbiosis of the gut microbiota. Patients with RA treated with DMARDs show partial restoration of eubiotic gut microbiome. Hence, it is essential to understand the impact of DMARDs on the microbial composition and its consequent influences on the host immune system to identify novel therapies for RA. In this review, we discuss the importance of antirheumatic-drug-induced host microbiota modulations and possible probiotics that can generate eubiosis.